Yield-scaled N2O emissions were effectively reduced by biochar amendment of sandy loam soil under maize - wheat rotation in the North China Plain. (December 2017) - Niu, Yuhui; Chen, Zengming; Müller, Christoph; Zaman, Monhammad M.; Kim, Donggill; Yu, Hongyan; Ding, Weixin
Abstract: It is increasingly recognized that the addition of biochar to soil has potential to mitigate climate change and increase soil fertility by enhancing carbon (C) storage. However, the effect of biochar on yield and nitrous oxide (N2 O) emissions from upland fields remains unclear. In this study, a one-year field experiment was conducted in an area of calcareous fluvo-aquic soil to assess and quantify the effect of maize straw biochar in reducing N2 O loss during 2014–2015 in the North China Plain. Eight treatments were designed as follows: no nitrogen (N) fertilizer (control, CK); biochar application at rates of 3 (B3), 6 (B6) and 12 (B12) t ha −1 ; chemical fertilizer (NPK) application at 200 kg N ha −1 (F); and fertilizer plus biochar application at rates of 3 (FB3), 6 (FB6) and 12 (FB12) t ha −1 . Crop yield, N2 O fluxes, soil mineral N concentrations, and soil auxiliary parameters were measured following the application of treatments during each season. During the maize growing season, N2 O emission was 0.57 kg N2 O-N ha −1 under CK treatment, and increased to 0.88, 0.93 and 1.10 kg N2 O-N ha −1 under B3, B6 and B12, respectively. In contrast, N2 O emissions were significantly reduced by 31.4–39.9% ( P < 0.05) under FB treatments compared with F, and the N2 O emission factor of the applied N was reduced from 1.36% under F to 0.71–0.85% under FB. There was also a significant interaction effect of fertilizer and biochar on N2 O emissions ( P < 0.01). During the wheat growing season, biochar had no effect on N2 O emissions regardless of the fertilizer regime. Biochar application did not affect maize yield; however, a significant increase in wheat yield of 16.6–25.9% ( P < 0.05) was observed without N fertilization. Nevertheless, a reduction in wheat yield was measured at a biochar rate of 12 t ha −1 with fertilization. Overall, under maize cropping, N2 O emissions per unit yield of grain, biomass, grain N and biomass N (yield-scaled N2 O emissions) were significantly reduced by 32.4–39.9% under FB compared with F treatment, regardless of the biochar application rate. Biochar did not affect yield-scaled N2 O emissions in wheat. Decreased soil bulk density with biochar is suggested to reduce the denitrification potential and N2 O emissions; while increased retention capacity of fertilizer N in biochar-added soil decreased wheat growth and yield. These findings suggest that N fertilization plus biochar application at 3 t ha −1 is a practical strategy for reducing yield-scaled N2 O emissions from maize fields in the North China Plain. Graphical abstract: Highlights: Interaction existed between biochar, N fertilizer and N2 O emissions. Biochar plus N fertilizer reduced N2 O emissions during maize growing season. Yield-scaled N2 O emissions during maize growing season were considerably reduced by biochar. Biochar application without N fertilization significantly increased wheat yield. Biochar at 3 t ha −1 is considered to be beneficial for yield and mitigating N2 O emissions.